The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/pc.23461
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of borate-modified expandable graphite and its flame retardancy on acrylonitrile-butadiene-styrene resin

Abstract: A borate-modified expandable graphite (written as MEG) was prepared through one step intercalating reaction of natural graphite, using KMnO 4 as oxidant, H 2 SO 4 and sodium tetraborate as intercalator and assistant intercalator, respectively. The dilatability, structure, element contents, thermal stability, and flame retardancy on acrylonitrile-butadiene-styrene (ABS) were investigated. Compared with the normal expandable graphite (written as EG, which was prepared with only H 2 SO 4 as intercalator), the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In addition, CO 2 , H 2 O, and SO 2 gases released in the redox reaction between graphite and H 2 SO 4 /HSO 4 − can dilute the concentration of flammable gas in the flame . Because of its excellent performance, EG is widely used as a flame retardant additive for polymer materials such as ethylene vinyl acetate (EVA) , polyolefin , acrylonitrile‐butadiene‐styrene (ABS) , epoxy resin , and silicone rubber . However, the used EG is commodity, and it is prepared by using H 2 SO 4 as an intercalating agent, which makes the GIC usually contain high levels of sulfate and release more SO 2 gas during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CO 2 , H 2 O, and SO 2 gases released in the redox reaction between graphite and H 2 SO 4 /HSO 4 − can dilute the concentration of flammable gas in the flame . Because of its excellent performance, EG is widely used as a flame retardant additive for polymer materials such as ethylene vinyl acetate (EVA) , polyolefin , acrylonitrile‐butadiene‐styrene (ABS) , epoxy resin , and silicone rubber . However, the used EG is commodity, and it is prepared by using H 2 SO 4 as an intercalating agent, which makes the GIC usually contain high levels of sulfate and release more SO 2 gas during combustion.…”
Section: Introductionmentioning
confidence: 99%
“…As a commercially available inorganic intumescent flame retardant (IFR), expandable graphite (EG) can expand in the perpendicular direction and generate a vermicular structured layer when exposed to heat source. [5][6][7] In contrast with the traditional chemical IFR consisting of ammonium polyphosphate/pentaerythritol/melamine (APP/PER/MEL), EG has a series of advantages, such as low cost, low toxicity, and good water and corrosion resistance. However, the worm-like intumescent char generated by EG upon burning or heating is usually fragile and fluffy and easily destroyed by heat convection and flame pressure during combustion process.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its outstanding mechanical and transport properties [10][11][12], in recent year graphene has attracted the attention of several researchers as a nanofiller for multifunctional composites. In fact, graphene-based nanocomposites are massively investigated [11,[13][14][15][16][17][18][19][20][21][22][23]. In particular, some studies on ABS with graphite/graphene as novel fillers were also reported.…”
Section: Introductionmentioning
confidence: 99%